Fundamentos para adoção do stare decisis em matéria tributária - Geraldi, Guilherme Paes de Barros (2023)
This thesis sought to find a solution to the problem of weakening legal certainty in Brazil due to constant jurisprudential changes regarding tax law. In order to do so, it was established as a hypothesis the possibility that the application, in the Brazilian legal system, of the doctrine of stare decisis, arising from the legal systems created based on the common law tradition, could solve, or at least mitigate, the problem of insecurity. in tax matters, caused by jurisprudential instability. To follow the path that starts from the hypothesis and arrives at the test of the thesis, it was analyzed what is the content of the principle of legal certainty and how the jurisprudential instability moves Brazilian tax law away from the ideal state of things desired by this legal principle. It was also analyzed how the legal systems built under the influence of the common law, which have recognized, for much longer than we have, the creative role of jurisprudence, deal with this situation of jurisprudential changes in the face of the principle of legal certainty. Once we have identified the mechanisms created by the common law to guarantee legal certainty in an environment that has jurisprudence as its main source of law, we investigate whether such mechanisms are applicable in the Brazilian legal system, reaching an affirmative conclusion. Finally, the thesis test was carried out, in order to demonstrate its usefulness, through the analysis of concrete situations in which there were jurisprudential changes in the tax field, proving that with the application of stare decisis, there are gains in terms of legal certainty